Analysis of the Volumes of the Posterior Cranial Fossa, Cerebellum, and Herniated Tonsils Using the Stereological Methods in Patients with Chiari Type I Malformation - Ümit Erkan Vurdem; Niyazi Acer; Tolga Ertekin; Ahmet Savranlar; Mehmet Fatih İnci (The Scientific World Journal)
Objective. The aim of this study was to determine the posterior cranial fossa volume, cerebellar volume, and herniated tonsillar volume in patients with chiari type I malformation and control subjects using stereological methods. Material and Methods. These volumes were estimated retrospectively using the Cavalieri principle as a point-counting technique. We used magnetic resonance images taken from 25 control subjects and 30 patients with chiari type I malformation. Results. The posterior cranial fossa volume in patients with chiari type I malformation was significantly smaller than the volume in the control subjects (P<0.05). In the chiari type I malformation group, the cerebellar volume was smaller than the control group, but this difference was not statistically significant (P>0.05). In the chiari type I malformation group, the ratio of cerebellar volume to posterior cranial fossa volume was higher than in the control group. We also found a positive correlation between the posterior cranial fossa volume and cerebellar volume for each of the groups (r=0.865, P<0.001). The mean (±SD) herniated tonsillar volume and length were 0.89±0.50 cm3 and 9.63±3.37 mm in the chiari type I malformation group, respectively. Conclusion. This study has shown that posterior cranial fossa and cerebellum volumes can be measured by stereological methods, and the ratio of these measurements can contribute to the evaluation of chiari type I malformation cases.